1999
DOI: 10.1016/s0168-8278(99)80137-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer to the rat biliary tract with the HVJ-cationic liposome method

Abstract: HVJ-cationic liposome-mediated gene transfer to the biliary tract via the papilla of Vater is a minimally-invasive and an effective gene-delivery method for site-specific targeting to the epithelial cells of the biliary tract, which could be applied to the treatment of human biliary tract diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The ß-galactosidase expression vector (pCAG-lacZ) was constructed as previously described [14]. HVJ cationic liposomes containing pCAG-lacZ (200 Ìg), previously incubated with 64 Ìg of a nuclear protein (the high mobility group 1 (HMG-1)), were prepared as described above for the HVJ cationic liposomes containing FITC-ODN.…”
Section: Preparation Of Hvj Cationic Liposomes Containing Pcag-lacz Amentioning
confidence: 99%
See 1 more Smart Citation
“…The ß-galactosidase expression vector (pCAG-lacZ) was constructed as previously described [14]. HVJ cationic liposomes containing pCAG-lacZ (200 Ìg), previously incubated with 64 Ìg of a nuclear protein (the high mobility group 1 (HMG-1)), were prepared as described above for the HVJ cationic liposomes containing FITC-ODN.…”
Section: Preparation Of Hvj Cationic Liposomes Containing Pcag-lacz Amentioning
confidence: 99%
“…In this vector system, the HVJ promotes fusion of the liposome with the surface membrane of targeted cells resulting in delivery of DNA directly into the cell [13]. Uehara et al [14] reported that the HVJ cationic liposome method was successful for selective gene transfer to bile duct epithelial cells in vivo. On the other hand, Kupffer cells have never been selectively targeted, although direct injection of HVJ liposomes into the liver was performed [15].…”
Section: Introductionmentioning
confidence: 99%
“…The complex offers good transfection efficiency with reduced immunogenicity compared to other viral systems, thus enabling repeated administration. This carrier has been used to efficiently deliver plasmids to the liver by both the portal vein as well as the biliary system (Uehara et al, 1999;Hirano et al, 2001). The HVJ has recently been used in a successful preclinical tumor therapy animal study (Hasegawa et al, 2001).…”
Section: Manipulation Of Intracellular Distribution Of Exogenous Dnamentioning
confidence: 99%
“…b-Galactosidase expression in bile duct epithelial cells was observed 3 d after the administration of HVJ-cationic liposomes containing pCAG-lacZ through the papilla of Vater in a rat model [1]. Intrabiliary administration of the adenovirus vector of the retinoblastoma (RB) gene [2] and the p53 gene [3] inhibited epithelial and fibrous tissue proliferation in a cholangitis model of rats.…”
Section: Introductionmentioning
confidence: 99%